Risk Factor PreHypertention and Hypertention at New Student at Universitas Muhammadiyah Maluku Utara - Tati Sumiati; Andiani Andiani; Tutik Lestari; Nani Supriyatni; Norma B. Toduho; La Arudin (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
Hypertension is a silent killer and is one of the challenges in the twenty-first century in improving public health. The increase in cases of hypertension in adolescents increases cases in adults, premature death and the most common case is essential hypertension which is asymptomatic and detected only during examination. New students in the transition of life demand changes including lifestyle that has the potential for health problems including hypertension. This study aims to determine the prevalence and risk factors for prehypertension and hypertension in new students at the Universitas Muhammadiyah Maluku Utara. The research method uses a quantitative approach with a cross-sectional design. The population in this study were new students of the Muhammadiyah University of North Maluku in the 2024/2025 academic year. A sample of 207 students. The sampling technique used accidental sampling. Data collection was carried out on August 26, 2024. Data analysis used chi-square to analyze the relationship between independent and dependent variables. The results of the analysis showed that 6.3% of respondents had hypertension and 35.3% had prehypertension. The most students (73.9%) had a Body Mass Index in the thin category, abdominal circumference at risk of 17.4%. The results of the analysis showed that there was a relationship between gender and prehypertension and hypertension. Men are 2.7 times at risk of experiencing prehypertension and hypertension compared to female students. BMI and Abdominal circumference were not related. The results of this study show that there are cases of hypertension in new students of UMMU and gender as a risk factor for hypertension, while Body Mass Index and abdominal circumference need further analysis related to the group of students who have a lot of thin Body Mass Index.